Structural Neuroimaging in Adults and Adolescents With Newly Diagnosed Focal Epilepsy: The Human Epilepsy Project. (8th November 2022) - Bank, Anna M.; Kuzniecky, Ruben; Knowlton, Robert C.; Cascino, Gregory D.; Jackson, Graeme; Pardoe, Heath R.; ,
Abstract : Background and Objectives: Identification of an epileptogenic lesion on structural neuroimaging in individuals with focal epilepsy is important for management and treatment planning. The objective of this study was to determine the frequency of MRI-identified potentially epileptogenic structural abnormalities in a large multicenter study of adolescent and adult patients with newly diagnosed focal epilepsy. Methods: Patients with a new diagnosis of focal epilepsy enrolled in the Human Epilepsy Project observational cohort study underwent 3 T brain MRI using a standardized protocol. Imaging findings were classified as normal, abnormal, or incidental. Abnormal findings were classified as focal or diffuse and as likely epilepsy-related or of unknown relationship to epilepsy. Fisher exact tests were performed to determine whether abnormal imaging or abnormality type was associated with clinical characteristics. Results: A total of 418 participants were enrolled. Two hundred eighteen participants (59.3%) had no abnormalities detected, 149 (35.6%) had abnormal imaging, and 21 (5.0%) had incidental findings. Seventy-eight participants (18.7%) had abnormalities that were considered epilepsy-related, and 71 (17.0%) had abnormalities of unknown relationship to epilepsy. Older participants were more likely to have imaging abnormalities, while participants with focal and epilepsy-related imaging abnormalities were younger than those without these abnormalities. One hundred thirty-one participants (31.3%) had a family history of epilepsy. Epilepsy-related abnormalities were not associated with participant sex, family history of epilepsy, or seizure type. Discussion: We found that 1 in 5 patients with newly diagnosed focal epilepsy has an MRI finding that is likely causative and may alter treatment options. An additional 1 in 5 patients has abnormalities of unknown significance. This information is important for patient counseling, prognostication, and management.